2021
DOI: 10.3390/plants10122778
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Potassium Pre-Harvest Applications on Fruit Quality and Condition of Sweet Cherry (Prunus avium L.) Cultivated under Plastic Covers in Southern Chile Orchards

Abstract: In rainy locations, sweet cherry is cultivated under plastic covers, which are useful to prevent fruit cracking but decrease cherry quality such as firmness and acidity. Here we evaluate the impact of pre-harvest K foliar applications on harvest and post-harvest fruit quality and condition of sweet cherry cultivated under plastic covers in southern Chile orchards. The study was performed on two commercial orchards (cv. Regina), located in different regions, during two consecutive seasons. In all cases, a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Our results on the composition of organic acids in Regina fruits revealed that the sum of organic acids detected in Regina fruits (malic, citric, tartaric, and oxalic) ranged from 1.19 to 1.51 g kg −1 of FW, depending on the treatment. These values were around 10-times lower than those reported by Kelebek and Selli [ 32 ], which could be explained by the reduced acidity of sweet cherry fruits produced in southern Chile previously reported by Bustamante et al [ 20 ] and Villavicencio et al [ 81 ]. In addition, we found that malic acid was the most abundant organic acid in fruits, followed by tartaric acid, oxalic acid, and citric acids.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Our results on the composition of organic acids in Regina fruits revealed that the sum of organic acids detected in Regina fruits (malic, citric, tartaric, and oxalic) ranged from 1.19 to 1.51 g kg −1 of FW, depending on the treatment. These values were around 10-times lower than those reported by Kelebek and Selli [ 32 ], which could be explained by the reduced acidity of sweet cherry fruits produced in southern Chile previously reported by Bustamante et al [ 20 ] and Villavicencio et al [ 81 ]. In addition, we found that malic acid was the most abundant organic acid in fruits, followed by tartaric acid, oxalic acid, and citric acids.…”
Section: Discussionmentioning
confidence: 54%
“…The use of plastic covers is one of the strategies used to mitigate the negative impacts of rainy weather on sweet cherry fruit production and quality. Although covers are useful in overcoming the harmful effect of rainfall during the bloom period and before harvest [ 36 ], they decrease fruit firmness and acidity [ 10 , 20 , 37 ], thus reducing fruit quality and overall condition. Otherwise, potassium (K) has been described as an important regulator of several parameters related to fruit yield and quality due to its functions as a catalyst and enzyme activator in different protein reactions and carbohydrate metabolisms [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations